Expression of c-kit protein in cancer versus normal breast tissue - Talaiezadeh, Abdolhassan; Jazayeri, Seyed Nematollah; Nateghi, Jamal (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : There are at least four main signal transduction pathways within human cells which are activated by interaction of an extracellular ligand with its corresponding receptors. One of them is activation of protein kinase. Actually, any of these proteins at any level of the signaling cascade in a human cell can undergo mutation and cause irregular cellular proliferation and finally result in cancer. C-kit is alternatively called stem cell factor receptor (SCFR) or CD117. It appears that lack of c-kit expression accompanies progression of some tumors, e.g. lung, breast, GIST. The aim of this study was to evaluate C-kit protein expression level within cancer cases. Material and methods : Sixty specimens of breast cancer and 60 non-cancerous breast tissue specimens were evaluated by IHC for C-kit presentation. We used positive GIST slides as controls. Epi-info ver 6.04 (CDC, WHO) was used for analysis. Results : C-kit was negative in all breast cancer specimens. C-kit was negative in 47 (78%) of 60 non-cancerous breast tissue specimens, but was positive in 13 (22%) of them (p < 0.0001). Conclusions: There is a reduction in C-kit expression with malignant transformation of breast epithelium. C-kit is believed to play a role in breast carcinogenesis. However, we should follow patients with normal or benign breast tissue to indicate any correlation between C-kit presentation and breast cancer development.